2011
DOI: 10.1016/j.jcmg.2011.04.021
|View full text |Cite
|
Sign up to set email alerts
|

CMR Evaluation of Cardiac Involvement During the Convalescence of Kawasaki Disease

Abstract: Kawasaki disease (KD) is a form of vasculitis affecting both the myocardium and coronary arteries. Coronary aneurysms develop in 15% to 25% of untreated patients (1,2). Myocardial inflammation is nearly universal during the acute phase (100% of cases in both post-mortem analysis and myocardial biopsy). However, there are no data about cardiac involvement during the convalescence of KD (1,2). Our aim was to evaluate the heart during the convalescence of KD by cardiac magnetic resonance (CMR). Thirteen KD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 4 publications
1
15
1
Order By: Relevance
“…However, a comparison with normal values was not reported, and although patients were reported to be reevaluated after 3 months, functional follow-up data were not described. 28 Several investigators have reported mean normal values for CMRI indexes in healthy subjects, but these studies overall reported lower biventricular EDV and ESV and higher EF than we found in the present study (Table 3). [33][34][35][36][37][38][39][40][41] The differences may be explained by the age range of the study population, the use of different CMRI techniques, and the use of different image analysis protocols.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…However, a comparison with normal values was not reported, and although patients were reported to be reevaluated after 3 months, functional follow-up data were not described. 28 Several investigators have reported mean normal values for CMRI indexes in healthy subjects, but these studies overall reported lower biventricular EDV and ESV and higher EF than we found in the present study (Table 3). [33][34][35][36][37][38][39][40][41] The differences may be explained by the age range of the study population, the use of different CMRI techniques, and the use of different image analysis protocols.…”
Section: Discussioncontrasting
confidence: 70%
“…Another and more likely explanation is that-in contrast to large areas of myocardium affected by ischemic processesthe prior myocarditis-related damage cannot be detected on CMRI because of its diffuse and limited nature. This is supported by a recent study by Mavrogeni et al 28 CMRIs were performed in 13 patients during the reconvalescence of KD (20-40 days after the onset of disease). Both early enhancement and T2-weighted analysis were highly suggestive of an active inflammatory process in 6 of 13 patients (46%).…”
Section: Discussionsupporting
confidence: 68%
“…[23] Novel CMR techniques, such as T1 mapping quantification, could potentially offer more thorough appreciation of possible prior myocarditis-related damage with diffuse and limited nature and its correlation to CMR-FT abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…7). Conventional digital subtraction coronary angiography is used in challenging cases where an invasive procedure is required [23,24].…”
Section: Kawasaki Diseasementioning
confidence: 99%